Descriptive analysis of routine childhood immunisation timelines in the Western Cape, South Africa - Blose, Ntombifuthi J (Department of Public Health and Family Medicine, 2022)
Background: Adherence to the recommended age-specific immunisation schedules is critical in ensuring vaccine effectiveness against vaccine preventable diseases (VPDs). Delays in the uptake of routine childhood immunisations lead to an increase in children susceptible to VPDs. Catch-up vaccination campaigns are strategies aimed at minimising the time at risk of VPDs and alleviating missed immunisation opportunities. However, there is limited data on immunisation timeliness in the Western Cape to contribute to developing effective catch-up vaccination campaigns. Therefore, this study sought to assess the timeliness of age-specific routine childhood immunisation within the Western Cape province of South Africa. Methods: We reviewed 709 participant records from a prospective health-facility based study conducted between 2012 and 2016 in Cape Town, South Africa. The primary outcome of interest was receiving age-specific immunisations ≥ 4 weeks (28 days) of that recommended for age as per the South African Expanded Programme on Immunisation (EPI) schedule. Using secondary data, the prevalence of delayed uptake of immunisations and time-at-risk for each vaccine was determined using proportions and medians and interquartile range (IQR). Multivariable logistic regression (p< 0.05) was used to determine the association between potential socio-economic risk factors and delayed uptake of routine childhood immunisations. Results: A total of 652/709 (91.9%) participants with a median age of 11 [IQR 4.5 – 28.0] months were eligible for analysis in this study. A trend of decreasing immunisation coverage with increasing age was observed among study participants. Notably, a trend of increasing delay in the uptake of routine vaccines and an increasing median time-at-risk of VPDs in age-specific immunisations was observed with increasing age. The highest delay in the uptake of vaccine doses was observed among the 3rd dose of the DTP3 vaccine 163 (34.6%), while the lowest was seen among the birth doses [(BCG – 40 (6.5%) and OPV – 43 (7%)]. The longest median time-at-risk of VPDs, was with the 2nd dose of the measles vaccine dose [12.9 (IQRs 6.7-38.6) weeks] and the lowest was OPV birth dose [6.3 (5.3-9.1) weeks]. Multivariable logistic regression analysis showed that participants who attended pre-school or creche compared to those who did not, were protected against delaying uptake of the 3 rd dose of the Hepatitis B vaccine and 2nd dose of the measles vaccine. While those who had adult caregivers compared to those who had adolescent caregivers, were protected against delaying the uptake of the 1 st rotavirus vaccine dose. Participants from households of low and upper-middle socio-economic IQR compared to high socio-economic status (SES) based on SES scores calculated from household data (i.e., availability and sources of amenities such as water, fuel, toilets, and level of maternal education) were more likely to delay uptake of the 3 rd does of the Pneumococcal Conjugate Vaccine and the 1 st dose of the measles vaccine, respectively. Conclusion: Using DTP3 coverage as proxy for national immunisation coverage, immunisation coverage in this population fell below the recommended 95% immunisation coverage rate. Additional population delays in the uptake of vaccine doses increases the time during which infants and children are susceptible to potential fatal VPDs. The observed increase in delayed immunisation and increased time-at-risk of VPDs, calls for an urgent need to address timing of vaccination particularly in late infancy and in the second year of life. There is an urgent need to develop strategies aimed at mitigating factors associated with delay in uptake of routine childhood vaccines in the Western Cape Province. Since creche attendance conferred protection against the delay in uptake of vaccines, mitigation strategies implemented upstream by the department of basic education, as well as health and immunisation service providers should strengthen collaborations to ensure that timely vaccine uptake among creche attendees is regularly monitored. Where delays are identified, catch-up strategies can be implemented at educational facilities or referrals to immunization clinics. It is important that this strategy is coupled with caregiver and healthcare worker vaccine education on the importance of timely immunisation uptake. Education about timely vaccine uptake will aid in the provision of informed council from healthcare providers to – not only adult caregivers - but adolescent caregivers as well, with the aim to reduce delayed uptake of vaccine amongst those raised by adolescent caregiver. The health system and the Expanded Programme of Immunisation on South Africa (EPISA) should couple these interventions with effective mobile reminder systems. These reminder systems will particularly serve the purpose to remind those caregivers whose delay uptake of vaccines as a result of a busy schedule. This could improve adherence to the recommended childhood immunisation schedule. Generally, for such interventions to work, effective monitoring and surveillance of immunisation services and vaccines is critical in achieving a high immunisation coverage and timely uptake of vaccines. Future studies should continuously monitor immunisation coverage and timeliness data in the Western Cape Province and South Africa as a whole to support evidence-based strengthening of provincial and national immunisation services.